Astaxantin Topikal Sebagai Terapi Adjuvan terhadap Kadar Serum Interleukin 8 pada Akne Vulgaris - Fiska Rosita; Putti Fatiharani Dewi; Muhammad Eko Irawanto; Rina Sidharta (Jurnal Health Sains, 2021)
Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebasea unit associated with the sebum glands. Reactive oxygen species play a role in av pathophysiology. Astaxantin has an anti-inflammatory effect so administration of this topical ASX is expected to cause improvement of lesions in AV. The purpose of the study was to find out that topical astaxantin can lower serum levels of interleukin-1(. This study is a clinical experimental study using the pre and post control design group design double-blind randomized controlled trial with 2 groups, namely the treatment group given standard AV therapy drugs in the form of gel containing tretinoin 0.025% + clindamycin phosphate 1.2% and astaxantin gel 5% and control group given the same standard AV therapy drug and placebo gel. Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebasea unit associated with the sebum glands. Reactive oxygen species play a role in av pathophysiology. Astaxantin has an anti-inflammatory effect so administration of this topical ASX is expected to cause improvement of lesions in AV. The purpose of the study was to find out that topical astaxantin can lower serum levels of interleukin-1(. This study is a clinical experimental study using the pre and post control design group design double-blind randomized controlled trial with 2 groups, namely the treatment group given standard AV therapy drugs in the form of gel containing tretinoin 0.025% + clindamycin phosphate 1.2% and astaxantin gel 5% and control group given the same standard AV therapy drug and placebo gel. Serum IL-8 levels were assessed at weeks 0 and VIII as an in vitro study. The paired difference between the serum IL-8 pretest and postest levels in the treatment group was p=0.751 and the control group was p=0.837. The unpaired test of il-8 level examination between the treatment group and the control group on the pretest was p=0.607 and the posttest was p=0.297 showed no significant difference. The addition of topical astaxantin as an AV supplemental therapy has not been shown to lower serum IL-8 levels.